Media Game Lumio untuk Penilaian Kognitif IPS Kelas 4 SDN Serua 01 Kota Tangerang Selatan - Putra, Jaelani Anton Pratama; Hadi, Muhamad Sofian (Fakultas Tarbiyah dan Ilmu Keguruan UIN Sultan Aji Muhammad Idris Samarinda, 2024)
Digital-based learning media has been widely used in the classroom learning process since the Covid-19 pandemic. There are many learning applications that can be an option for teachers as learning media, one of which is Lumio. This study aims to determine the use of Lumio learning media in creating a fun learning atmosphere and the use of Lumio in the cognitive assessment process in social studies learning in class 4 of SDN Serua 01 Tangerang Selatan. This type of research is qualitative research. The method used is descriptive analysis. The data analysis technique is thematic analysis where researchers use questionnaires to determine the effectiveness of Lumio in creating a fun learning atmosphere through the cognitive assessment applied. There are three stages in this study, namely the preparation stage, the implementation stage, and the evaluation stage. The results of the study show that social studies learning using Lumio learning media can make the learning atmosphere feel more fun and make the cognitive assessment process easier with various unique quiz variants that are enjoyed by students.